2008
DOI: 10.1111/j.1600-051x.2007.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of tacrolimus 0.1% ointment and clobetasol 0.05% ointment in patients with oral lichen planus

Abstract: Background: Oral lichen planus (OLP) is considered to be an autoimmune disease of unknown aetiology that affects the mucosae, especially the oral cavity. Objective: We compared tacrolimus 0.1% ointment and clobetasol 0.05% ointment for the treatment of OLP. Patients and Methods: A total of 32 patients (20 females and 12 males; all white, Italian origin, mean age of 43.6 AE 18.4 years; 16 patients per treatment group) were treated with tacrolimus or clobetasol ointment for 4 weeks in a randomized, double-blind,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(133 citation statements)
references
References 23 publications
0
127
1
2
Order By: Relevance
“…Two recent randomized trials reported that tacrolimus was more effective than topical corticosteroids (triamcinolone and clobetasol) in controlling painful symptoms of erosive OLP (26,27). However, another randomized, double-blind study found no significant differences between tacrolimus and clobetasol in the management of symptomatic OLP (28).…”
Section: Discussionmentioning
confidence: 89%
“…Two recent randomized trials reported that tacrolimus was more effective than topical corticosteroids (triamcinolone and clobetasol) in controlling painful symptoms of erosive OLP (26,27). However, another randomized, double-blind study found no significant differences between tacrolimus and clobetasol in the management of symptomatic OLP (28).…”
Section: Discussionmentioning
confidence: 89%
“…Se ha comparado su eficacia frente a la de los retinoides tópicos, y se ha visto que los preparados de Tacrólimus al 0,1% resultan más efectivos que el propionato de clobetasol al 0,05% en el tratamiento del LPO (46). Sin embargo, los autores reconocen en este estudio que para poder defender el uso de inmunosupresores para el tratamiento de esta enfermedad hacen falta todavía estudios llevados a cabo en poblaciones más grandes.…”
Section: Tacrólimusunclassified
“…Topical tacrolimus was used in four trials [13,22,23,35], topical pimecrolimus in four trials [15,17,24,33], topical cyclosporine in four trials [3,5,14,16].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[18] all the participants received a systemic steroid, and in another study [28] the experimental intervention was compared with intralesional steroid. Of the 29 trials using steroid as an active intervention, clobetasol was used in nine trials [4,7,10,11,19,22,23,27,35], triamcinolone in ten trials [4,5,[13][14][15][16]20,28,31,36], flucinolone in two trials [6,8], dexamethasone in two trials [29,34], prednisolone in one trial [18], fluticasone in one trial [9] & betamethasone in two trials [9,20]. Systemic prednisolone was used in one trial [18].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation